Polytraumatism in childhood - it can be more than it seems!. - Peres, Ana (2010)
Thoracic injuries can occur in 50% of polytraumatized children, but rupture of the airway is extremely rare. We describe the case of a three-year-old child victim of fall of fourth floor, with head, spine, thoracic and abdominal trauma. On admission she had left side hemothorax and hypertensive pneumothorax and a chest drainage was inserted. Imagiological studies showed left lung contusion, fracture of L1-L4 with spinal cord bone splint and spinal cord injury (D11-L3). On day 3, because of hematic chest drainage and persistent left lung opacity, a bronchoscopy was performed and showed total section of the left main bronchus. She underwent surgical reconstruction of the bronchial tree with atypical resection of the lower lobe of the left lung, with good recovery. This case demonstrates the complexity and the importance of the multidisciplinary approach to the polytraumatized child.